Prediction of the aerodynamic effect of model deformation during transonic wind tunnel tests. (1st January 2013) - Mouton, Sylvain; Le Sant, Yves; Lyonnet, Marianne
During wind tunnel tests, any aircraft model deforms as a result of aerodynamic loads. This behaviour is generally regarded as a spurious effect of the testing technique that needs to be accounted for and corrected. This paper presents available optical technique to measure wing deformation in ONERA wind tunnels, and introduces a simulation method to predict the effect of the deformation on the model aerodynamic characteristics.